Effect of Injector Needle Tip Shape on Jet Flow for Pelton Turbine - Chun Zhang; Chao Wang; Qianhe Tian; Quanwei Liang; Yilin Zhu; Yexiang Xiao; Yong Bai; Zhaoning Wang; Hengte Zhou; Xianwu Luo (Energies)
The Pelton turbine has been widely applied for the advantages of its simple structure, flexible mass flow rate, wide range of applicable heads and high efficiency. The nozzle and needle are a core part of the Pelton turbine injector. In this paper, the VOF (Volume of Fluid) model was used to simulate the jet flow behaviors and hydraulic performance for a Pelton injector with a needle tip with different breakage losses. Three types of needle tip breakage loss combined with normal needle tip were selected for numerical calculation and analysis, focusing on the influence of needle tip on the high-speed jet flow characteristics. An injector with normal needle tip hydraulic performance is compared with the model test. Finally, the injector hydraulic performance and the jet flow behavior changes with the needle tip shape were comprehensively analyzed. Results show that the needle tip shape almost does not affect the flow rate; when the tip breakage loss is larger than 0.1 of nozzle diameter, the jet efficiency will decrease rapidly and the jet will diffuse rapidly after outflow from the injector. The investigation provides a basis for the operation, maintenance and stability of the Pelton turbine.